Worlds that could not be Utopia in Chronicles, Ezra and Nehemiah - Schweitzer, Steven James; Uhlenbruch, Frauke (New York Bloomsbury T&T Clark, 2016)
Introduction -- Testing utopia as a contemporary method in biblical studies -- "Worlds that could not be: Is Thomas More's Utopia modern?" -- Terje Stordalen, University of Oslo, Norway -- "'Utopia where it is to be hoped that the coffee is a little less sour'?: Dr Who's 'Utopia' and Chronicles" -- Gerrie Snyman, University of South Africa, South Africa -- "King Solomon or King Utopus?: A game of utopian pastiche in 2 Chronicles 1-9" -- Frauke Uhlenbruch, independent scholar -- After exile, under empire: utopian identity negotiations in Ezra-Nehemiah and Chronicles -- "Exile, empire, and prophecy: reframing utopian concerns in Chronicles" -- Steven J. Schweitzer, Bethany Theological Seminary, USA -- "Writing and the Chronicler: authorship, ambivalence, and utopia" -- Donald Polaski, Randolph-Macon College, USA -- "Re-negotiating a putative utopia and the stories of the rejection of foreign wives in Ezra-Nehemiah" -- Ehud Ben Zvi, University of Alberta, Canada -- "Antagonized utopia in Ezra-Nehemiah" -- Jeremiah Cataldo, Grand Valley State University, USA -- Searching for the place: theologies of utopia -- "Taking the reader into utopia" -- Matthias Jendrek, Theological Faculty Paderborn, Germany -- "Searching the 'place' in Chronicles: a u-topia?" -- Thomas Willi, University Greifswald, Germany -- Response: Utopia and its use by Biblical Scholars as seen by a utopian scholar -- Vincent Geoghegan, Queens University Belfast, UK -- Bibliography -- Index
The idea of Utopia was first made current and popular by Sir Thomas More with the publication of his book by the same name in 1516. The 'no-place' that was created has had a fantastic reception history, which makes its application to the biblical books of Nehemiah, Ezra and Chronicles as vibrant as the current scholarship which is ongoing into the Renaissance term and its implications. The essays in this collection take different approaches to the question: are there proto-utopian elements in the three books from the Hebrew Bible? Methodological considerations are to be found, but each essay also moves beyond the methodological constraint to raise the hypothetical question of 'what if?' in different ways. The essays evaluate the potential, and pitfalls, of reading Biblical books as (proto-)utopian. Topics include how utopia construct intricate counter-realities, and how to tell whether a proposal diagnosed as 'utopian' from a modern point of view is meant to motivate its audience to political action. Case studies which read aspects of Chronicles, Ezra and Nehemiah as potential utopian traits include the restoration project of Ezra-Nehemiah and the rejection of foreign wives, utopian concerns in Chronicles, as well as the empire's role in writing a putative utopia, and King Solomon as a utopian fantasy-king
Includes bibliographical references and index
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Utopias -- Biblical teaching; Konferenzschrift; Konferenzschrift -- 2013 -- Baltimore; Konferenzschrift -- 2014 -- Wien